Rencana Penataan Permukiman Berbasis Community Action Plan sebagai Instrumen Pemulihan Pascabencana yang Berkelanjutan: Studi Kasus Huntap Satelit Desa Sibalaya Selatan, Kabupaten Sigi - Budi Andresi; Nadine Sandra Agustina; Dita Septyana (Fakultas Teknik Universitas Cenderawasih, 2026)
Post-disaster settlement recovery requires more than the provision of permanent housing; it demands an integrated approach covering social, economic, institutional, environmental, and disaster risk reduction dimensions. This study analyzes the Settlement Planning Document (RPP) of the Sibalaya Selatan Satellite Permanent Resettlement Area (Huntap) in Sigi Regency, Central Sulawesi, which accommodates 118 households displaced by the 2018 Palu liquefaction disaster. The research examines the RPP as a participatory planning instrument for sustainable post-disaster recovery. A qualitative participatory approach using the Community Action Plan (CAP) method was conducted from July to November 2024 through focus group discussions, participatory workshops, formation of a Core Planning Team (TIP), field observations, document reviews, and public consultations. Data were analyzed using descriptive, infrastructure, spatial, and strengths-problems-opportunities-challenges frameworks. The findings reveal that community social capital, reflected in active organizations, social networks, and digital communication infrastructure, has been transformed into economic capital. In addition, four dimensions of community resilience economic, social, communication, and competence capacities were identified at varying levels of development. The TIP also played a strategic role in integrating the RPP into village and regional development planning. The resulting RPP contains 39 priority programs valued at approximately IDR 340.6 million for 2024-2028 across infrastructure, economic, social-environmental, and disaster risk reduction sectors. The study demonstrates that the CAP approach effectively supports sustainable settlement development and offers a replicable model for post-disaster resettlement areas in Indonesia.